2022
DOI: 10.1039/d2tb01198k
|View full text |Cite
|
Sign up to set email alerts
|

Controllable preparation of bioactive open porous microspheres for tissue engineering

Abstract: Biodegradable microspheres have been widely applied as cell carriers for tissue engineering and regenerative medicine. However, most cell carriers only have simple planar structure and show poor biological activity and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Uniform and appropriate particle size may affect cell adhesion and proliferation. [3,46] The MSs made at 1500 rpm rotation speed are the most suitable size for cell culture, as their water content is the highest and is able to provide oxygen and nutrients to the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Uniform and appropriate particle size may affect cell adhesion and proliferation. [3,46] The MSs made at 1500 rpm rotation speed are the most suitable size for cell culture, as their water content is the highest and is able to provide oxygen and nutrients to the cells.…”
Section: Discussionmentioning
confidence: 99%
“…1a. The porosity of MSW20 is denser than that of WP and MSW10, and a denser porosity facilitates the spread of molecules and the exchange of nutrients and waste products inside composites [37]. Hydrogels with three-dimensional network structures can swell in water and avoid autolysis.…”
Section: Morphology and Analysis Of The Compositionmentioning
confidence: 99%
“…In recent years, various studies on the diameter and number of pores of microspheres have attracted increasing attentions [28,29]. The early study by Hulbert et al reported that the minimal pore size for bone regeneration was in the range of 75-100 µm [30].…”
Section: Characteristics Types and Compositions Of Microspheresmentioning
confidence: 99%